The strategies and mechanisms of enteroviruses to evade innate immunity and the vaccine progress of enteroviruses - Yin, Yangqi; Chi, Xuyang; Feng, Yandong; Jiang, Qinglian (Frontiers in Cellular and Infection Microbiology, 2025)
Enteroviruses (EVs) are a group of highly contagious RNA viruses that can cause a wide range of diseases, from mild infections to severe complications like neurological disorders and myocarditis. This review focuses on the innate immune evasion strategies employed by EVs, highlighting their mechanisms and consequences. EVs evade host immune responses through various tactics, including inhibiting pathogen recognition receptors (PRRs) such as toll-like receptors (TLRs) and RIG-I-like receptors (RLRs), disrupting key signaling pathways like nuclear factor kappa-B (NF-κB) and (JAK)-signal transducers and activators of transcription (STAT), and directly targeting interferon (IFN) signaling components. Specific viral proteases, such as 2A protease (2Apro) and 3C protease (3Cpro), play crucial roles in these evasion strategies by cleaving host proteins involved in immune signaling. Additionally, EVs manipulate host factors to suppress antiviral responses, exemplified by the upregulation of proteins like sex-determining region Y-box 4 (Sox4) and microRNAs (miRNAs) that inhibit TLR signaling. The review also discusses the development of vaccines against EVs, emphasizing the importance of prophylactic measures in controlling infections. Understanding these immune evasion mechanisms is essential for developing effective antiviral therapies and vaccines.